(untitled) (Research, Society and Development, 2024)
Dental fluorosis is a dental condition characterized by the manifestation of white spots on permanent teeth, resulting from excessive exposure to fluoride during tooth development. While fluoride is recognized for its benefits in preventing tooth decay, its excess can lead to aesthetic changes in dental enamel. The aim of this article is to present an alternative for the clinical case of a patient with suggestive signs of dental fluorosis in the upper central incisors. The proposed intervention to improve dental aesthetics involved removing the superficial layer of enamel through chemical and mechanical erosion using a microabrasive (6.6% hydrochloric acid and silicon chloride) followed by combined teeth whitening. This resulted in a more uniform and aesthetically pleasing appearance. Therefore, the combination of these procedures proved effective in the conservative treatment of dental fluorosis, with operational ease and affordable cost.